Ownership structure and earnings management: Empirical evidence from Vietnam - Huu Anh Nguyen; Quynh Lien Le; Vu Thi Kim Anh (Cogent Business & Management, 2021)
This paper examines the relationship between ownership structure and earnings management in Vietnam. The governance structure of companies in Vietnam is characterized by the dominance of largest shareholders, who often makes significant influences on direct or indirect management decisions. Existing literature shows that the ownership structure has a significant effect on earnings management. Therefore, the main purpose of this paper is to analyze how the company's ownership structure affects earnings management. Using the sample from 489 non-financial companies listed on the Vietnam stock market, we found that ownership concentration and state ownership positively affect earnings management. In contrast, the managerial ownership and foreign ownership negatively affects earnings management. Furthermore, among the five control variables, Board size; Cash flow are positively related, while financial performance, company size and financial leverage negatively affect earnings management.
Keywords: M41; 650; earnings management; ownership structure; listed companies; Vietnam